Behavioral Interventions can Mitigate Adverse Pregnancy Outcomes Among Women Conceiving on ART and Those Initiated on ART During Pregnancy: Findings From the MOTIVATE Trial in Southwestern Kenya. (1st January 2021) - Onono, Maricianah; Odwar, Tobias; Wahome, Samuel; Helova, Anna; Bukusi, Elizabeth Anne; Hampanda, Karen; Turan, Janet; Abuogi, Lisa
Abstract : Background: Antiretroviral therapy (ART) is essential for the elimination of mother-to-child transmission and improved health outcomes for women living with HIV (WLWH). However, adverse pregnancy outcomes (APOs) among pregnant women on ART are a growing concern. Methods: We investigated the associations between timing of ART initiation and APOs among pregnant WLWH receiving behavioral interventions (community mentor mothers and text messaging) in the Mother-Infant Visit Adherence and Treatment Engagement (MOTIVATE) study in southwestern Kenya. Log binomial models were used for estimation of relative risks (RRs) (adjusted for the clustered nature of data) evaluating APOs with 3 exposure comparisons: (1) preconception ART initiation vs. postconception initiation; (2) among postconception ART initiating women, comparisons across gestational ages at cART initiation (first versus second and third trimester exposure), and (3) intervention allocation. Results: Of the 1275 women included in this analysis, 388 (30%) had an APO: 306 preterm births, 38 low birth weight infants, 33 stillbirths, and 11 miscarriages. In multivariable analysis, viral load ≥1000 copies/mL, moderate and severe anemia at baseline increased risk of APOs. Among women initiating ART before and after conception, no difference was observed in the composite APO. Women who received community mentor mother visits alone (aRR 0.74: 95% CI: 0.71 to 0.76) or text messages alone (aRR 0.79: 95% CI: 0.70 to 0.89) had lower risks of experiencing any APOs. Conclusions: Receiving supportive behavioral interventions may mitigate the risk of experiencing an APO among WLWH on ART. Further studies are needed to investigate the underlying mechanisms and optimize the benefits of these interventions.